2020
DOI: 10.3389/fpls.2020.00787
|View full text |Cite
|
Sign up to set email alerts
|

Linking Short-Chain N-Acyl Homoserine Lactone-Mediated Quorum Sensing and Replant Disease: A Case Study of Rehmannia glutinosa

Abstract: Li et al. Quorum Sensing Modulate Replant Disease R. glutinosa. In conclusion, consecutive monoculture of R. glutinosa contributed to the imbalance between beneficial and harmful short-chain AHL-mediated QS bacteria in the rhizosphere, which was mediated not only by specific root exudates but also by the QQ bacterial community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…have shown that microbiomes of the plants that survived under pathogenesis were associated with the specific rare taxa, namely, the highly pathogen-suppressing Pseudomonas and Bacillus bacteria . Li et al studied the functional relation of AHL producing quorum-sensing bacteria in the rhizomicrobiome with the suppression of plant pathogens . Quorum-sensing bacteria belonging to the Pseudomonas genus showed strong antagonistic activities against Fusarium oxysporum or Aspergillus flavus, the two main causal agents of Rehmannia glutinosa root rot disease …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…have shown that microbiomes of the plants that survived under pathogenesis were associated with the specific rare taxa, namely, the highly pathogen-suppressing Pseudomonas and Bacillus bacteria . Li et al studied the functional relation of AHL producing quorum-sensing bacteria in the rhizomicrobiome with the suppression of plant pathogens . Quorum-sensing bacteria belonging to the Pseudomonas genus showed strong antagonistic activities against Fusarium oxysporum or Aspergillus flavus, the two main causal agents of Rehmannia glutinosa root rot disease …”
Section: Resultsmentioning
confidence: 99%
“…4 Li et al studied the functional relation of AHL producing quorum-sensing bacteria in the rhizomicrobiome with the suppression of plant pathogens. 53 Quorum-sensing bacteria belonging to the Pseudomonas genus showed strong antagonistic activities against Fusarium oxysporum or Aspergillus flavus, the two main causal agents of Rehmannia glutinosa root rot disease. 53 A variety of nanoparticles have been shown to trigger the phytohormone-mediated defense cycle in plants to tackle the pathogenesis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5 The study of continuous cropping obstacles of Chinese medicinal materials demonstrates that gallic acid, salicylic acid, syringic acid, vanillic acid and protocatechuic acid are the main phenolic acids leading to allelopathy of common genuine medicinal materials such as Panax notoginseng , Rehmannia glutinosa , Panax quinquefolium , Pseudostellaria heterophylla , Salvia miltiorrhiza and Pinellia ternate . 6 Li et al 3 found that in the root exudates of Rehmannia glutinosa , a phenolic acid mixture had an inhibitory effect on the growth of beneficial pathogens, while the effect on the growth of harmful pathogens was the opposite, so Rehmannia glutinosa showed strong pathogenicity. In summary, it was necessary to collect, extract, separate and then analyse phenolics in the natural environment to determine their allelopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that phenolic acids are the most identied and most active allelochemicals in the plant soil environment. 2,3 Phenolic acids are a class of organic acids with simple structures containing aromatic phenolic rings, phenolic hydroxyl groups and carboxyl groups. In soil, phenolics can occur in the three following forms: free, reversibly bound, and bound forms.…”
Section: Introductionmentioning
confidence: 99%
“…and harmful (Enterobacter spp.) short-chain AHL-mediated QS (quorum sensing) bacteria balance in the rhizosphere, accounting for a key factor of R. glutinosa replant diseases [14].…”
mentioning
confidence: 99%